1D and 2D Polybromotellurates(IV): Structural Studies and Thermal Stability. Issue 27 (20th July 2018) - Usoltsev, Andrey N.; Adonin, Sergey A.; Abramov, Pavel A.; Novikov, Alexander S.; Shayapov, Vladimir R.; Plyusnin, Pavel E.; Korolkov, Ilya V.; Sokolov, Maxim N.; Fedin, Vladimir P.
Abstract : Three novel polybromotellurates(IV) were obtained by reactions of TeO2 in conc. HBr with Br2 and tri‐ or tetraalkylammonium salts. They contain [TeBr6 ] 2– octahedra connected by Br2 linkers into one‐ or pseudo‐two‐dimensional networks. The thermal stability of the products was investigated by TGA; additionally, all compounds were characterized by Raman spectroscopy. Energies of Br··· Br interactions were estimated by DFT calculations (QTAIM method). Abstract : In the presence of tri‐ or tetraalkylammonium cations, [TeBr6 ] 2– and Br2 form one‐ or two‐dimensional supramolecular polybromide/bromotellurate hybrids demonstrating remarkable stability.